Answer:
see explanation
Explanation:
first we calculate the slopes of EF and FG using the slope formula
m =
![(y_(2)-y_(1) )/(x_(2)-x_(1) )](https://img.qammunity.org/2023/formulas/mathematics/college/jkzrkt8zi557egkc0ias6wietjfal5swo6.png)
with (x₁, y₁ = E (7, 7 ) and F (4, 8 )
=
=
= -
![(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/rshimc01547v0bylxspiig5y5rp1hyhlbx.png)
repeat with (x₁, y₁ ) = F (4, 8 ) and (x₂, y₂ ) = G (2, 2 )
=
=
= 3
if 2 lines are perpendicular then the product of their slopes = - 1
here
×
= -
× 3 = - 1
then EF is perpendicular to FG